A new Technique For Solving Fractional Nonlinear Equations By Sumudu Transform and Adomian Decomposition Method - Gatea Mousa, Maad; Altaie, Huda Omran (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
A novel technique Sumudu transform Adomian decomposition method (STADM), is employed to handle some kinds of nonlinear time-fractional equations. We demonstrate that this method finds the solution without discretization or restrictive assumptions. This method is efficient, simple to implement, and produces good results. The fractional derivative is described in the Caputo sense. The solutions are obtained using STADM, and the results show that the suggested technique is valid and applicable and provides a more refined convergent series solution. The MATLAB software carried out all the computations and graphics. Moreover, a graphical representation was made for the solution of some examples. For integer and fractional order problems, solution graphs are shown. The results confirmed that the accuracy of this technique converges to the integer order of the issues.